2020
DOI: 10.1111/joim.13204
|View full text |Cite
|
Sign up to set email alerts
|

The circadian syndrome predicts cardiovascular disease better than metabolic syndrome in Chinese adults

Abstract: Background. To compare the predictive value of the circadian syndrome (CircS) and Metabolic syndrome (MetS) for cardiovascular disease.Method. We used the data of 9360 Chinese adults aged ≥40 years from the 2011 China Health and Retirement Longitudinal Study (CHARLS). Of the participants, 8253 people were followed in the 2015 survey. MetS was defined using the harmonized criteria. CircS was based on the components of the International Diabetes Federation (IDF) MetS plus short sleep and depression. The cut-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 31 publications
5
43
0
Order By: Relevance
“…The concept of CircS was first proposed by Zimmet et al in 2019 based on the concept of MetS and then defined with a cutoff value by Shi et al (12,15). In the definition of CircS, another two risk factors, which were depression and reduced sleep duration, were clustered with the components of MetS including abdominal obesity, hypertension, hyperglycemia, high triglycerides, and low high-density lipoprotein (HDL) cholesterol.…”
Section: Measurements Of Variables: Circs and Luts/bphmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of CircS was first proposed by Zimmet et al in 2019 based on the concept of MetS and then defined with a cutoff value by Shi et al (12,15). In the definition of CircS, another two risk factors, which were depression and reduced sleep duration, were clustered with the components of MetS including abdominal obesity, hypertension, hyperglycemia, high triglycerides, and low high-density lipoprotein (HDL) cholesterol.…”
Section: Measurements Of Variables: Circs and Luts/bphmentioning
confidence: 99%
“…The specific cutoff values of the seven components in CircS and MetS were presented in Supplementary Table 1. According to one previous study, the cutoff for MetS was set as ≥3 components, while for CircS, the cutoff was ≥4 components (15).…”
Section: Measurements Of Variables: Circs and Luts/bphmentioning
confidence: 99%
See 2 more Smart Citations
“…Circadian dysfunction has been proposed and defined as the presence of any four of the following seven traits, including elevated waist circumference, elevated triglycerides, reduced high-density lipoprotein (HDL)-cholesterol, elevated blood pressure, elevated fasting glucose, short sleep duration (<6 h/day), and the depression symptom ( 7 ). Shi et al ( 11 ) assessed the association between circadian syndrome and cardiovascular disease (CVD), and the result also suggested that the circadian syndrome was a strong predictor for CVD occurrence. However, to the best of our knowledge, there has been no study that examined the association between circadian syndrome and stroke so far.…”
Section: Introductionmentioning
confidence: 99%